34z+63=-17z+471

Simple and best practice solution for 34z+63=-17z+471 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 34z+63=-17z+471 equation:


Simplifying
34z + 63 = -17z + 471

Reorder the terms:
63 + 34z = -17z + 471

Reorder the terms:
63 + 34z = 471 + -17z

Solving
63 + 34z = 471 + -17z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '17z' to each side of the equation.
63 + 34z + 17z = 471 + -17z + 17z

Combine like terms: 34z + 17z = 51z
63 + 51z = 471 + -17z + 17z

Combine like terms: -17z + 17z = 0
63 + 51z = 471 + 0
63 + 51z = 471

Add '-63' to each side of the equation.
63 + -63 + 51z = 471 + -63

Combine like terms: 63 + -63 = 0
0 + 51z = 471 + -63
51z = 471 + -63

Combine like terms: 471 + -63 = 408
51z = 408

Divide each side by '51'.
z = 8

Simplifying
z = 8

See similar equations:

| 2/3(z-2)-11/3=-5 | | 5x+33=98 | | 10-10d=20 | | 2v=21 | | -80+-4x=120+6x | | (x+1)(x-1)=(x+1)(x-2) | | -80x+-4x=120+6x | | 3x-19=-70 | | 23-5=110 | | -(6y+1)-(-5y-8)=0 | | 3x^2-24x+28=0 | | 83overx=7 | | 3h-7=-7 | | -2(x-2)=-4x+14 | | -5-(-5/2) | | 33x-2+12x+2=180 | | -5/2-(-5/4) | | 33x-2+12+2=180 | | -75-11x=46 | | 6v-4=-2(v-2) | | 8/5k-3/2k= | | K/12-1=-3 | | x^3/x^6 | | c=1075 | | (64x^5y^-4z^9)^-2/3 | | 12x+102=-66 | | 3+(2d-5)=2+(2d-4) | | (2lnx-(lnx)^2)/x | | 416/13 | | X^2-2+4x^2=18 | | 28=4x+8(x-7) | | (b*2.8)+83=39 |

Equations solver categories